Stakeholder perspectives on implementation of internet-delivered cognitive behaviour therapy in physical medicine rehabilitation setting using the Consolidated Framework for Implementation Research - Swati Mehta; Ujjoyinee Barua; Marcie Nugent; Kevin Hansen; Luvish Sondhi; Randy Upper; Dalton Wolfe; Eldon Roh; Keith Sequeira; Robert Teasell; Heather D. Hadjistavropoulos (Journal of Rehabilitation Medicine)
Introduction: Despite the growing evidence for the effects of tailored internet-delivered cognitive behaviour therapy (ICBT) programmes for those receiving physical rehabilitation, there is a lack of implementation of these programmes in a clinical or community setting. The aim of the current study was to evaluate barriers and facilitators of implementing an ICBT programme into a physical medicine rehabilitation setting.